Non-native freshwater fish from drainages of Rio Grande do Sul State, Brazil - Vinicius de Araújo Bertaco; Marco Aurélio Azevedo (Papéis Avulsos de Zoologia, 2023)
Abstract The present study catalogues exotic and allochthonous fish species found in the three main freshwater river drainages of Rio Grande do Sul State using records of scientific collections and literature, and discusses the main impacts caused by their introduction in natural environments. Ten exotic species are found in the area, i.e., Clarias gariepinus, Coptodon rendalli, Ctenopharyngodon idella, Cyprinus carpio, Hypophthalmichthys molitrix, Hypophthalmichthys nobilis, Ictalurus punctatus, Micropterus salmoides, Oncorhynchus mykiss and Oreochromis niloticus, belonging to five orders, nine genera and seven families. These fishes are native from African, Asian, European and North American countries. The eight allochthonous species, i.e., Acestrorhynchus pantaneiro, Hoplerythrinus unitaeniatus, Hoplias lacerdae, Megaleporinus macrocephalus, Piaractus mesopotamicus, Pachyurus bonariensis, Serrasalmus maculatus, and Trachelyopterus lucenai, belong to three orders, eight genera, and six families, are native from the Río La Plata basin, that includes the Río Uruguay, and have been all registered in the Laguna dos Patos. Two of these species are further recorded in the Rio Tramandaí system (A. pantaneiro and T. lucenai). The study also presentes a brief history of the first records of exotic species in the state and in the country, and their main vectors of introduction. According to the records of exotic species in scientific collections, the two exotic species with the highest number of records in the country are tilapias Coptodon rendalii (508 records) and Oreochromis niloticus (376 records), and most records occurred in the last two decades. The two carps Cyprinus carpio and Ctenopharyngodon idella are the only exotic species recorded in the three main drainage basins of the state. In addition, we warn about the importance of studies about the biology and negative impacts of exotic species over native species on the understanding of management in wild environments.